A Case of Myxoma Arising in the Buccal Mucosa. (16th August 2021) - Okubo, Masahiko; Sano, Yoshie; Fukushima, Yosuke; Tomoda, Taketo; Kokabu, Shoichiro; Sato, Tsuyoshi
Abstract : Myxomas arising in the oral and maxillofacial areas are extremely rare. This study reports a case of myxoma arising in the soft tissue beneath the buccal mucosa of an 86-year-old man.